Size Charge Fractionation for the Characterization Investigation of Municipal Solid Waste Incinerator Fly Ash - Wu, Yanyu; Peng, Xiaochun; Hu, Xiaoying (Asian Journal of Chemistry, 2013)
A thorough examination has been undertaken for determining size dependent characterization of fly ash from municipal solid waste incinerators. The fly ash was segregated into five fractions and their size dependent characteristics, including particle size distribution, morphology, mineralogical and chemical composition, leaching behaviour of heavy metals of ash particles, levels of polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans were analyzed and evaluated. The results revealed that various size particles of fly ash have different characteristic due to transportation and mixing system inside incinerators. Particle size distribution indicated that 72.2, 82.4 and 91.4 % of fly ash have lower than 75, 125 and 187.5 μm, respectively. The leaching concentration of Pb in all fractions exceeded the regulatory level set by the China EPA. The leaching concentration of Cu, Zn and Pb of fly ashes with sized range 125-187.5 μm was lower than that of the others, whereas Cr had the highest concentration compared with other samples. The concentrations of higher-chlorinated congeners of dioxins were remarkably higher than those of lower-chlorinated congeners. The poison effect of dioxins in the fly ash was mainly caused by polychlorinated dibenzofurans. This investigation demonstrated that the characterization of municipal solid waste incinerator fly ash had the potential size dependent information of particulate materials in relation to their production processes, chemical compositions, environmental fates and other factors. The result was also provided the valuable information for incinerator design and operation.